2023
DOI: 10.3389/fpubh.2023.1076217
|View full text |Cite|
|
Sign up to set email alerts
|

Use of tobacco, nicotine and cannabis products among students in Switzerland

Abstract: IntroductionMost people who smoke cigarettes begin in their teens and teens may also be attracted to new tobacco, nicotine, and cannabis products. We describe use prevalence among upper-secondary school students in Switzerland, including daily use, of tobacco, nicotine, and cannabis products.MethodsWe invited secondary school students (age 15 to 21) in two Swiss cantons to take an online survey between October 2021 and February 2022. The survey collected demographic information and asked how frequently they us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Overall, like studies in other countries, this study suggested an extremely low prevalence of use of TFNPs among Dutch youth. Similar to the Netherlands, a study of 9,515 Swiss secondary school students aged between 15 and 21, conducted in late 2021/early 2022, reported a low prevalence of current infrequent TFNP use and a very low prevalence of frequent (daily) use of TFNPs [80]. Overall, these studies indicated that the use of TFNPs was less prevalent than tobacco-containing products, such as cigarettes, snus, snuff, and hookah, which are reported to contain more toxicants than those without tobacco and are, therefore, likely to be more harmful.…”
Section: Motivation and Intention To Use Tfnps Among Youthmentioning
confidence: 85%
“…Overall, like studies in other countries, this study suggested an extremely low prevalence of use of TFNPs among Dutch youth. Similar to the Netherlands, a study of 9,515 Swiss secondary school students aged between 15 and 21, conducted in late 2021/early 2022, reported a low prevalence of current infrequent TFNP use and a very low prevalence of frequent (daily) use of TFNPs [80]. Overall, these studies indicated that the use of TFNPs was less prevalent than tobacco-containing products, such as cigarettes, snus, snuff, and hookah, which are reported to contain more toxicants than those without tobacco and are, therefore, likely to be more harmful.…”
Section: Motivation and Intention To Use Tfnps Among Youthmentioning
confidence: 85%